Teacher Performance in Improving the Quality of Education in Man 4 Pandeglang - Iwan Setiawan; Anis Zohariah; Abdul Mui`in (International Journal of Advanced Technology and Social Sciences, 2023)
This research aims to evaluate teacher performance in an effort to improve the quality of education at MAN 4 Pandeglang. Improving the quality of education is an urgent need in the Indonesian education system. Teacher performance is one of the key factors in achieving this goal. This research method uses a qualitative approach by collecting data through interviews, observation and document analysis. The respondents in this research were teachers at MAN 4 Pandeglang. The research results show that teacher performance has a significant role in improving the quality of education in the school. Factors that influence teacher performance include motivation, competence, organizational support, and work environment.  This research also identified some of the obstacles faced by teachers in improving their performance, such as lack of resources and high work pressure. The results of this research can become a basis for schools and the government in designing programs and policies that support improving teacher performance. Thus, it is hoped that the quality of education at MAN 4 Pandeglang can continue to be improved, so as to produce a generation that is more qualified and ready to face future challenges